The Global Diffusion of Social Innovations – An Analysis of Twitter Communication Networks Related to Inclusive Education - Schuster, Johannes; Kolleck, Nina (Frontiers in Education, 2020)
In recent decades, different social innovations – such as lifelong learning, inclusion or Education for Sustainable Development – have had a huge impact on domestic education systems. In an increasingly globalized world, innovations diffuse across national borders. At the same time, diffusion processes seem to be highly influenced by public and private actors, e.g. international organizations (IOs) or non-governmental organizations (NGOs). Both state and non-state actors use social networks and digital communication platforms, such as Twitter, as channels for the diffusion of social innovations and practices. Inclusive education, which has become the main alternative to special schools for the schooling of children with disabilities, is a widely discussed innovation in education and, hence, represents a suitable case for the study of global diffusion processes and the involved actors. Thus, drawing on social network theory, the aim of this paper is to examine the structure of the Twitter communication network forming around the social innovation of inclusive education. Empirically, we use social network analysis to map the communication network; identify central actors; and infer assumptions about the role of different actor groups. Our results show, for instance, that especially NGOs and IOs hold central positions in the network, which enables them to exert influence on the diffusion of innovative ideas. Overall, the findings of our study indicate how the online communication tool Twitter can play a crucial role for actors who seek to influence the global diffusion of social innovations in education and effect education policies, norms and systems at the global, national and regional levels as such.